STUDY ON THE MECHANISM OF INFLUENCE OF INTERNAL GEAR RING FLEXIBILITY ON THE BIAS LOAD BEHAVIOR OF AERONAUTICAL PLANETARY GEAR SYSTEM - DING Shuo; LUO Yuan; LI Ming; NING Yongxu (Jixie qiangdu)
The planetary gear system is widely used in aircraft transmission equipment because of its small size, light weight and large load capacity，but the problem of bias load caused by various errors cannot be avoided, and a serious bias load condition will lead to under utilization of the advantages of the planetary system cannot be fully exploited.The influence mechanism of the flexible change of the inner gear ring on the bias load behavior of the system was investigated by taking a certain type of aeronautical planetary gear system as the research object.The deflection，stress and strain of the inner gear ring were measured by experiments with different number of planets and different rim thicknesses, and the mechanism of bias load was analyzed and the degree of influence of the number of planets and rim thickness on the bias load behavior of the system was evaluated.The advanced simulation calculation and analysis of a large aeronautical planetary system was completed by using a hierarchical finite element model to quantify the influence mechanism of the variation of inner gear ring flexibility on the load distribution and gear ring deflection of the system.The accuracy of the simulation results was evaluated by fitting the experimental and simulation results to the same parameter range for comparison.The research results provide targeted structural optimization guidance for the development and design of internal gear rings of large aeronautical planetary gear systems, which can greatly reduce the cost of this type of large aeronautical equipment in the design and iteration process.